The rise of the therapeutic state - Polsky, Andrew Joseph (Princeton, N.J. : Princeton University Press, 1991)
Assuming that ""marginal"" citizens cannot govern their own lives, proponents of the therapeutic state urge casework intervention to reshape the attitudes and behaviors of those who live outside the social mainstream. Thus the victims of poverty, delinquency, family violence, and other problems are to be ""normalized."" But ""normalize, "" to Andrew Polsky, is a term that ""jars the ear, as well it should when we consider what this effort is all about."" Here he investigates the broad network of public agencies that adopt the casework approach.
Book Cover -- Title -- Copyright -- Contents
Includes bibliographical references (pages 225-281) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Public welfare -- United States -- History; Human services -- United States -- History; Social work with people with social disabilities -- United States -- History; Aide sociale -- États-Unis -- Histoire; Services sociaux -- États-Unis -- Histoire; Service social aux personnes socialement défavorisées -- États-Unis -- Histoire; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; SOCIAL SCIENCE -- Human Services; SOCIAL SCIENCE -- Social Work; Human services; Public welfare; Social work with people with social disabilities; United States; Maatschappelijk werkers; Armoede; Verzorgingsstaat; Therapeutische processen; Marginaliteit; Randgroepen; Sociale dienstverlening; Maatschappelijk werk; Welzijnswerkers; Welfare services; United States; History